On Translatability - Iser, Wolfgang (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
This essay addresses the question of translatability as a key concept for understanding encounters between cultures and interactions within cultures. In this view, translatability implies translation of otherness without subsuming it under preconceived notions. In conclusion, this essay proposes a cybernetic model of cultural understanding based on recursive looping.